Effect of Topical Steroid on Swallowing Following ACDF: Results of a Prospective Double-Blind Randomized Control Trial. Issue 7 (1st April 2021) - Kim, Han Jo; Alluri, Ram; Stein, Dan; Lebl, Darren; Huang, Russel; Lafage, Renaud; Bennett, Tianna; Lafage, Virginie; Albert, Todd
Abstract : Study Design: Randomized, double-blinded, controlled trial. Objective: To investigate the effectiveness of local intraoperative corticosteroids at decreasing the severity of swallowing difficulty following multilevel anterior cervical discectomy and fusion (ACDF). Summary of Background Data: Dysphagia is a common complication after ACDF, and while for most patients the symptoms are mild and transient, some patients can suffer from severe dysphagia resulting in significant postoperative morbidity. Previous studies investigating the local application of corticosteroids are limited. Methods: This was a prospective, randomized, double-blinded, controlled trial of patients undergoing 2, 3, or 4 level ACDF for radiculopathy and/or myelopathy. Patients undergoing multilevel ACDF were randomized to receive local corticosteroid in the retropharyngeal space or placebo (no steroid). Dysphagia was assessed using validated outcomes including the Eating Assessment Tool-10 (Eat-10) and Swallowing Quality of Life (SWAL-QOL) Questionnaire both preoperatively and at 1 day (POD1), 2 days (POD2), and 1-month postoperatively. Results: One-hundred nine patients had a complete dataset available for analysis. Eat-10 scores were significantly lower in the Steroid group on POD2 (8 vs. 16, P  = 0.03) and 1-month postoperatively (2 vs. 5, P  = 0.03). A comparison of the individual SWAL-QOL subscale scores demonstrated that patients in the Steroid group had better scores than the Control group in various subscales at all postoperative time points. Significant differences were noted (always in favor of the Steroid group) in 40% of subscales on POD1, 60% of subscales on POD2, and 50% of subscales at 1-month postoperatively. The Control group never had a better SWAL-QOL subscale score at any time point postoperatively. Conclusion: Local administration of corticosteroid after multilevel ACDF can decrease postoperative severity and symptomatology of dysphagia during the immediate postoperative period to 1-month postoperatively. The long-term effects of local steroid administration on fusion and other complications will need to be established in future studies. Level of Evidence: 1 Abstract : Patients undergoing ACDF were randomized to receive local corticosteroid in the retropharyngeal space or placebo (no steroid). Validated dysphagia scores were significantly better at all postoperative time points in the patients receiving local corticosteroid.